2019
DOI: 10.1016/j.neuroimage.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

BOLD hemodynamic response function changes significantly with healthy aging

Abstract: Functional magnetic resonance imaging (fMRI) has been used to infer age-differences in neural activity from the hemodynamic response function (HRF) that characterizes the blood-oxygen-level-dependent (BOLD) signal over time. BOLD literature in healthy aging lacks consensus in age-related HRF changes, the nature of those changes, and their implications for measurement of age differences in brain function. Between-study discrepancies could be due to small sample sizes, analysis techniques, and/or physiologic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(138 citation statements)
references
References 93 publications
9
125
1
3
Order By: Relevance
“…Indeed many fMRI studies have shown that the amplitude of the blood-oxygen-level-dependent (BOLD) signal decreases with age (Tekes et al, 2005;Ances et al, 2009;Ward et al, 2015). Particularly interesting is a recent human fMRI study (West et al, 2019) which showed that, under visual stimulation, the BOLD signal in the occipital region of the old adult group had significantly lower peak amplitude, longer peak latency and slower rise slope compared to the young adult group. These age-related changes of the BOLD response were remarkably similar to what we observed in our neural data (Figure 2).…”
Section: Implication On Hemodynamic Signals During Healthy Agingmentioning
confidence: 99%
“…Indeed many fMRI studies have shown that the amplitude of the blood-oxygen-level-dependent (BOLD) signal decreases with age (Tekes et al, 2005;Ances et al, 2009;Ward et al, 2015). Particularly interesting is a recent human fMRI study (West et al, 2019) which showed that, under visual stimulation, the BOLD signal in the occipital region of the old adult group had significantly lower peak amplitude, longer peak latency and slower rise slope compared to the young adult group. These age-related changes of the BOLD response were remarkably similar to what we observed in our neural data (Figure 2).…”
Section: Implication On Hemodynamic Signals During Healthy Agingmentioning
confidence: 99%
“…Though, other interpretations exist. For instance, activation of language areas could be related to a carry-over effect specific to the older group due to changes in the deployment of the BOLD response (West et al, 2019). Alternatively, it is possible that older participants remained unconsciously thinking about semantic categories during the performance of the motor task or that they covertly pace themselves using inner speech/sub articulation.…”
Section: The Effects Of Sex Vocabulary and Educationmentioning
confidence: 99%
“…Age was included as a covariate because healthy aging can significantly impact the BOLD response (West et al, 2019). Significance was set to p < 0.05 for these comparisons.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For the blocked-design fMRI analysis, age, sex, and scanner were included as covariates in the voxel-wise regression analyses. Age was included as a covariate because healthy aging can significantly impact the BOLD response (West et al, 2019). Gender differences in hemodynamic responses have also been reported (Kastrup, Li, Glover, Kruger, & Moseley, 1999;Kaufmann, Elbel, Gossl, Putz, & Auer, 2001;Minhas, Panerai, & Robinson, 2018), and so we included gender as a covariate as well.…”
Section: Statistical Analysesmentioning
confidence: 99%